2008
DOI: 10.1016/j.parkreldis.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit aspects of sequence learning in pre-symptomatic Huntington's disease

Abstract: Learning deficits may be part of the early symptoms of Huntington's disease (HD). Here we characterized implicit and explicit aspects of sequence learning in eleven pre-symptomatic HD gene carriers (pHD) and eleven normal controls. Subjects moved a cursor on a digitizing tablet and performed the following tasks: SEQ: learning to anticipate the appearance of a target sequence in two blocks; VSEQ: learning a sequence by attending to the display without moving for one block, and by moving to the sequence in a suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 37 publications
4
39
1
1
Order By: Relevance
“…This indicates that both prodromal and symptomatic HD patients are impaired on a spatial-based implicit contextual cueing task. These results are in line with previous studies that have shown deficits for different types of implicit learning in prodromal HD participants (Gabrieli et al, 1997;Ghilardi et al, 2008;Heindel et al, 1989;Kim et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that both prodromal and symptomatic HD patients are impaired on a spatial-based implicit contextual cueing task. These results are in line with previous studies that have shown deficits for different types of implicit learning in prodromal HD participants (Gabrieli et al, 1997;Ghilardi et al, 2008;Heindel et al, 1989;Kim et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The striatum (including the caudate nucleus and putamen) is a part of the basal ganglia, which are a group of subcortical nuclei that are important for executive and motor functions, but are also involved in learning mechanisms. Prodromal HD patients have been found to be impaired on tasks that are dependent on the striatum, in particular implicit learning tasks, such as motor pursuit (Heindel, Salmon, Shults, Walicke, & Butters, 1989), rotary pursuit (Gabrieli, Stebbins, Singh, Willingham, & Goetz, 1997), mirror reading, and implicit sequence learning (Ghilardi et al, 2008;Kim et al, 2004). Implicit contextual learning is a type of implicit learning that has received much attention over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…This result, and the finding that motor performance improvement was consolidated (Ďľ24 h), corroborate and expend previous studies that found comparable results in similar motor tasks involved physical training of finger movements (Walker et al 2003). In our study, we can exclude the possibility that subjects learned the order sequence of the targets, or anticipated the targets, for four potential reasons: 1) targets were fixed and visible to the subjects (i.e., in our task there was not a reaction time requirement); 2) arm movement velocity dropped to zero at each arm movement (i.e., there was not anticipation from target to target); 3) our findings show the opposite of what is found in because previous sequence learning studies (Ghilardi et al 2008;Moisello et al 2009), which have nicely demonstrated that movements become anticipatory, movement duration increases while peak velocity and acceleration decrease; and 4) if there was an improvement in the acquisition of the order of the elements in the sequence, subjects of the active control group (i.e., eye movement training) should have improved their performance as well but did not.…”
Section: Sequential Order Learning Versus Improvement Of the Sequencecontrasting
confidence: 65%
“…Evidence suggests that a loss of circadian timing reduces the ability of the hippocampus to encode learned information [143]. This may be relevant in HD, since impaired declarative memory has been found in HD patients, including presymptomatic gene carriers [54]. It is possible, therefore, that the memory deficits found in HD are related in part to a reduction in SWS and/or circadian disturbances.…”
Section: The Consequences Of Disturbed Sleep In Hdmentioning
confidence: 99%